Effect of some medicinal plant extracts to combat disease worm (Ectomyelois ceratoniaezeller) in the date Deglet Nour (phoenix dactyliieraL.) - Hamada, Samra; Belhamra (University of eloued جامعة الوادي, 2017)
The varietyDeglet NourPhoenx dactytifera is the most famous and exporters date with an annual production of 26.5 million q/years. Because of the spread of some diseases and pests, especially worm dates Ectomyelois ceratoniae, as well as birds are harmful to its production marvelous is lost annually between 2O% to 30%, therefore the objective of this research, comes within the framework of agricultural development of wealth fruit of the date palms, and developing comprehensive strategy to combat diseases tree date palm. Applications of modern research appeared to àontrol crop pestJând vegetables, using of bioactive natural products as herbals, to protect agricultural production and human health. The first step of this research is the identification of medic]nal plants collected, and selected of more than 20 plants, and to know the nature of the Principe activé ingredients in each plant'As for the effect-of some extracts applied, we find an influence effectively à percentage the death of the worm: Alllum sativum (peel and cloves of garlic),Artemisia herbà aba, i-hapsia garganica, Teucrium polium, Euphorbia peptus, Solanum tuberosum, Papaver somniferum, punica gratum, and Camellia slnensi. The tested plant extracts are efficacy to combat against a disease worm dates Ecfomyelois ceratoniae, and we can use them as insecticideô.
4ème Congrès International de la Biodiversité Végétale – Marrakech 2017 مراكش - المغرب
Keywords: Deglet nour, Phoenix dactylifera, Ectomyetois ceratoniee, medicinal plant extracts.